2018
DOI: 10.16986/huje.2018038527
|View full text |Cite
|
Sign up to set email alerts
|

Lise Öğrencilerinin Yaşam Doyumu ve Yılmazlık Düzeylerinin Anne-Baba Tutumlarıyla İlişkisi Açısından İncelenmesi

Abstract: Bu araştırmanın amacı; lise öğrencilerinin yaşam doyumu ve yılmazlık düzeylerinin anne-baba tutumlarına göre incelenmesidir. Bununla birlikte öğrencilerin yaşam doyumu ve yılmazlık düzeylerinin cinsiyete ve algılanan akademik başarıya göre farklılaşma düzeylerini ve yaşam doyumu ve ana-baba tutumlarının yılmazlığı anlamlı bir şekilde yordayıp yordamadığını araştırmaktır. Araştırmanın çalışma grubunu İstanbul ve Kocaeli'nde farklı liselerde eğitim gören 679 (Meslek Lisesi, İmam-Hatip Lisesi, Fen Lisesi ve Anado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
1
2
0
2
Order By: Relevance
“…It is seen that the feelings and thoughts of the students are compatible with each other. There are similar studies supporting these results regarding students' academic and professional future concerns (Aydın & Çiftel, 2013;Çiftçi-Arıdağ & Ünsal-Seydooğulları, 2019;Dursun & Özkan, 2019).…”
Section: çAlışma Grubusupporting
confidence: 59%
“…It is seen that the feelings and thoughts of the students are compatible with each other. There are similar studies supporting these results regarding students' academic and professional future concerns (Aydın & Çiftel, 2013;Çiftçi-Arıdağ & Ünsal-Seydooğulları, 2019;Dursun & Özkan, 2019).…”
Section: çAlışma Grubusupporting
confidence: 59%
“…Werner (1993) states that especially girls have better cognitive and reading skills and are more resilient than children who develop problems later. While there are study findings in the literature (Erdem, 2017;Gundas & Kocak, 2015;Onat, 2010;Sun & Stewart, 2007), some studies have reported that resilience levels do not cause a significant difference in terms of gender (Ciftci Aridag & Unsal Seydoogullari, 2018;Erkoc, 2019). However, in some studies (Bahadir Yilmaz & Oz, 2015;Lazaridou & Beka, 2014), the resilience levels of boys were found to be higher than girls.…”
Section: Results For the First Research Questionmentioning
confidence: 99%
“…This difference was in favor of those with high educational status probably due to the fact that as the education level increases, parental attitudes become more democratic, and parents' social-emotional development such as getting help, communication, empathy, and protective relationships are supported more by parents. While authoritarian parents prevent the child from gaining experience due to their strict discipline and punishment (Eldeleklioglu, 1996), democratic parents create the most positive environment for their children 's identity and personality development with unconditional love and respect (Ciftci Aridag & Unsal Seydoogullari, 2018). In the study conducted by Ogelman (2015), to examine the predictive effect of parents' acceptance-rejection levels on the resilience of their preschool children, a negative and strong correlation was found between the neglect/indifference and aggression/hostility levels of the fathers and the resilience levels of the children.…”
Section: Results For the First Research Questionmentioning
confidence: 99%
“…Çalışmada, okul öncesi çocukların ego sağlamlığının cinsiyete göre anlamlı bir farklılık göstermediği belirlenmiştir. Ego sağlamlığı konusunda yapılan araştırmalara bakıldığında çocukların cinsiyeti ve yaşı ile ego sağlamlığı arasında anlamlı bir ilişki olmadığı saptanmıştır (Çiftçi Arıdağ ve Ünsal Seydooğulları, 2018;Erkoç, 2019;Önder vd., 2016Önder vd., . Taylor ve diğerleri (2013 yapmış oldukları çalışmada okul öncesi dönemde çocukların ego sağlamlık düzeylerinin cinsiyete göre farklılaşmadığını belirtmişlerdir.…”
Section: Tartişma Ve Sonuçunclassified